INTEGRASI NILAI – NILAI ISLAM DAN BUDAYA ORGANISASI DI BAPPEDA ACEH BARAT DALAM KERANGKA RASIONALITAS BIROKRASI - Olta Meniza; Ligar Abdillah; Sopar Sopar (Jurnal Society : Pengamat Perubahan Sosial, 2026)
BAPPEDA is a regional agency that carries out the task of coordinating the preparation, approval, and evaluation of the implementation of regional development plans. This research was conducted to examine how Islamic values are applied in the West Aceh BAPPEDA, given the very high workload, and how religious normative values are integrated into administrative practices and bureaucratic behavior. This study contributes to the field of organizational sociology by demonstrating that the integration of Islamic values into organizational culture establishes normative mechanisms that strengthen institutional performance. The method used in this research is qualitative, which can reveal community life, history, behavior, organizational functionality, social movements, and kinship relationships. Data was obtained through several data collection processes, namely observation, interviews, and documentation. The results of this research indicate that the integration of Islamic values, such as reciting prayers before starting work, being honest in work, being responsible, and being open to the regional development planning process, is being implemented. The application of Islamic values in West Aceh BAPPEDA demonstrates a bureaucratic model that is not only efficient but also oriented toward a balance between work rationality and religious morality, ultimately strengthening the organization's overall legitimacy and effectiveness. Organizational culture and the integration of Islamic values at the West Aceh BAPPEDA go hand in hand in shaping a bureaucracy that is both rational and morally valuable.